2013
DOI: 10.1007/978-1-62703-426-5_3
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral Imaging and Automated Laser Capture Microdissection of Human Cortical Neurons: A Quantitative Study of CXCR4 Expression

Abstract: Summary Quantifying protein and RNA expression within specific cell populations in vivo is an essential step in unraveling the complex mechanisms of neurological disease. The challenges associated with studying human brain tissue is commonly compounded by variations in post-mortem interval, formalin fixation time, and tissue processing among others. The result is a sample population that is inherently heterogeneous, requiring a single protocol that is sensitive to low levels of antigen while minimizing backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Immunohistochemistry was performed as previously reported, with modifications (Pitcher et al, 2013). Paraffin blocks containing mPFC were sectioned at 5-µm thickness on a microtome.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry was performed as previously reported, with modifications (Pitcher et al, 2013). Paraffin blocks containing mPFC were sectioned at 5-µm thickness on a microtome.…”
Section: Methodsmentioning
confidence: 99%
“…Imaging and analysis was performed as previously described (Pitcher et al, 2013), with modifications. Briefly, fluorescent microscopy coupled with multispectral image analysis was used to identify individual neurons immunostained for NeuN (Cell Signaling Technology 24307, 1:400) within layer 2/3 of the mPFC prelimbic region.…”
Section: Methodsmentioning
confidence: 99%
“…Postmortem frontal cortex tissue of both humans and rhesus macaques was formalin fixed and paraffin embedded for immuno histo chemistry analyses. The dual staining immuno histochemistry protocol was previously described in greater detail (72). Tissue was sequentially dual-stained with the neuronal marker MAP2 (Chemicon, 1:250) and the protein of interest: FHC (Abcam, 1:50), pCXCR4 (Abcam, 1:50), or CXCR4 (1:100).…”
Section: Methodsmentioning
confidence: 99%
“…Imaging and analysis of dual-stained human and rhesus macaque cortex was previously described in detail (72). Briefly, brightfield microscopy coupled with multispectral image analysis was performed to identify individual MAP2 + neurons within the cortex and measure the absolute OD of the given antigen of interest (FHC, CXCR4, or pCXCR4) within each individual MAP2 + neuron.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Fends et al [ 38 ] demonstrated a rapid immunostaining technique for fresh frozen sections using tissues from neoplasmic lymph nodes, the breast, and the prostate, in combination with LCM, which allowed the recovery of high-quality mRNA. As to paraffin embedded human cortical neurons, Pitcher et al [ 37 ] reported an effective immunohistochemistry protocol for quantitative analysis of protein and RNA expressions using LCM (PALMRobo).…”
Section: Discussionmentioning
confidence: 99%